PELABELAN TOTAL TIDAK TERATUR TITIK GRAF UNIDENTIFIED FLYING OBJECT - Andi Daniah Pahrany; Nurdin Nurdin; Hasmawati Hasmawati (UNIVERSITAS NEGERI MALANG, 2022)
For a graph G that have vertex set V and edge set E. A labelling f:VUE->1,2,3,...,k is called a vertex irregularity total k-labeling of G if for any two different vertices x and y in V have wt(x)≠ wt(y) where wt(x)=f(x)+∑_yV(G) f(xy). The smallest positive integer k such that G has a vertex irregular total k-labeling is called the total vertex irregularity strength of G , denoted by tvs(G).In this paper, we determined the total vertex irregularity strength of Unidentified Flying Object Graph, tvs(U_(m,n). The result in this paper as follows: tvs(U_m,n)=(3n+1)/2 for 3<=m<=3((n+1)/2), n>=3, andtvs(U_m,n)=(3n+m)/3 for m>3((n+1)/2), n>=3.